Synthesis and character of a functionally-graded aluminium titanate/zirconia-alumina composite - Pratapa, Suminar (Curtin University, 1997)
A functionally-graded Al(subscript)2TiO(subscript)5/ZrO(subscript)2-Al(subscript)2O(subscript)3 (AT/zirconia-alumina) composite has been successfully synthesized by an infiltration process involving an alpha-Al(subscript)2O(subscript)3-ZrO(subscript)2 (90:10 by weight) green body and a solution containing titanium chloride. The mass gain after infiltration has been used to estimate the amount of new phase introduced into the system. The phase composition character of the functionally-graded material (FGM) has been determined by x-ray diffraction. The Rietveld "whole pattern" refinement method was applied to diffraction patterns of the sample which were collected from the surface and at several depths which were made by polishing away the material. Absolute weight fraction determination using the Rietveld external standard method showed that the concentration of AT reduces linearly from the surface to the core. In contrast, the alpha-alumina content increases with depth in a complementary manner. Low level amorphous phase was also observed. Other functionally-graded microstructural profiles examined were x-ray characteristic line intensity of Ti, Ti dot-mapping, and alpha-alumina grain size. The FGM also exhibits graded character in both thermal and mechanical properties, i.e. thermal expansion, microhardness, and Young's modulus. The thermal expansion coefficient (TEC) of the FGM increased with polishing-depth and approached that of the zirconia-alumina reference sample at a depth of 0.5 mm.Relatively lower thermal expansion and softer surface layer in comparison to those of the core (TEC value of 5.9 x 10(subscript)-6 degrees celsius(subscript)-1 and microhardness of 6 GPa compared to 7.4 x 10(subscript)-6 degrees celsius(subscript)-1 and 12 GPa, respectively) render possibilities to implement the material to which thermal shock resistance surface but hard core, such as a metal melting crucible, are required. Load-dependent microhardness was obviously observed on the surface of the material but only slight dependence was observed in the core. This observation indicated that the material exhibit "quasi-ductile" surface but brittle core. In comparison to the reference specimen, the FGM displayed damage-tolerance and remarkable machinability.